Evidence-based medicine and ethics: a practical approach. Issue 2 (13th April 2004) - Vineis, P
Abstract : The clinical decision is supposed to be based on evidence. In fact, what counts as evidence is far from being established. Some definition of "proof" is needed to distinguish between scientific medicine and charlatanism. My thesis is that unfortunately a clear-cut boundary between evidence and lack of evidence cannot be found, for several reasons that I summarise in the paper. Evidence in medicine very often has fuzzy boundaries, and dichotomising fuzziness and uncertainty can have serious consequences. Physicians and patients should accept the irreducible fuzziness of many of the concepts they use when dealing with health and disease.